Education on clean and healthy living behavior and wise use of medicine at the Al-Qur'an Tahfidz Boarding School Jami' Baitusshalihin [Edukasi perilaku hidup bersih dan sehat serta bijak menggunakan obat di Pesantren Tahfidz Al-Qur'an Jami' Baitusshalihin] - Tedy Kurniawan Bakri; S Suryawati; Hijra Novia Suardi; Heru Fahlevi; Shylvana Adella; Rudi Dharma; Cut Melda Meriyana; R Raihanah (Buletin Pengabdian Bulletin of Community Services, 2024)
A healthy and clean environment can be created starting from self-awareness and the surrounding community. A clean environment fosters a healthy life and is free from various diseases. Clean and Healthy Living Behavior (PHBS) is an action to prevent the occurrence of diseases and improve health levels. Disease disorders caused by poor sanitation in the boarding school environment certainly require further treatment, one of which is by consuming certain drugs. The steps in obtaining, using, storing, and disposing of drugs need to be known by students in order to maximize the healing of their illnesses. The purpose of this service is to increase awareness among students about the importance of maintaining personal and environmental hygiene, as well as to provide the right knowledge about the use of drugs. The methods used in this community service include lectures, discussions, educational videos, and simulations. The results of this community service indicate an increase in the understanding and knowledge of students regarding clean living patterns. Boarding school managers also gained a better understanding of the importance of proper sanitation in the boarding school environment and how to use drugs properly and correctly. In conclusion, there is an increase in students' understanding of clean-living patterns and knowledge of how to use drugs appropriately.